2003
DOI: 10.14214/sf.503
|View full text |Cite
|
Sign up to set email alerts
|

Effects of wood, peat and coal ash fertilization on Scots pine foliar nutrient concentrations and growth on afforested former agricultural peat soils

Abstract: Hytönen, J. 2003. Effects of wood, peat and coal ash fertilization on Scots pine foliar nutrient concentrations and growth on afforested former agricultural peat soils. Silva Fennica 37(2): 219-234.The effects of ash and commercial fertilizers on the foliar nutrient concentrations and stand growth of Scots pine were studied in four fi eld experiments established on former cultivated peat soils. The aims were to compare ash types (wood, peat and coal ash), study the effects of ash treatment (pelletization), com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
1
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 11 publications
4
27
1
2
Order By: Relevance
“…Patterson et al (2004) found a total P concentration of 0.6% in wood waste ash (wood, bark, and knots). In investigations by Erich and Ohno (1992), Saarsalmi et al (2001), and Hytönen (2003) wood ashes contained 0.9-1.7% P. In general, hardwood ash has more P than ash of softwood (Pitman 2006). P concentrations of more than 1% were detected in peat ash (1.3%, Hytönen 2003), in saw dust ash (1.3%, Awodun 2007), and in different straw ashes: wheat straw ash (1.3%), barley straw ash (1.7%), rye straw ash (1.6%), and rape straw ash (2.1%) (Sander and Andrén 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patterson et al (2004) found a total P concentration of 0.6% in wood waste ash (wood, bark, and knots). In investigations by Erich and Ohno (1992), Saarsalmi et al (2001), and Hytönen (2003) wood ashes contained 0.9-1.7% P. In general, hardwood ash has more P than ash of softwood (Pitman 2006). P concentrations of more than 1% were detected in peat ash (1.3%, Hytönen 2003), in saw dust ash (1.3%, Awodun 2007), and in different straw ashes: wheat straw ash (1.3%), barley straw ash (1.7%), rye straw ash (1.6%), and rape straw ash (2.1%) (Sander and Andrén 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In investigations by Erich and Ohno (1992), Saarsalmi et al (2001), and Hytönen (2003) wood ashes contained 0.9-1.7% P. In general, hardwood ash has more P than ash of softwood (Pitman 2006). P concentrations of more than 1% were detected in peat ash (1.3%, Hytönen 2003), in saw dust ash (1.3%, Awodun 2007), and in different straw ashes: wheat straw ash (1.3%), barley straw ash (1.7%), rye straw ash (1.6%), and rape straw ash (2.1%) (Sander and Andrén 1997). For sewage sludge ashes, a total P concentration from 2 to 9% can be assumed (Jakobsen and Willett 1986;Zhang et al 2002;Franz 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The objectives of our work were to evaluate the P fertilizing effect of biomass ashes on different soils, and to investigate possible interactions between the effects of ashes and cultivated crops. (Jamil et al 2004) 0.01 Alfalfa stem ash (Mozaffari et al 2002) 0.90 Horticulture ashes (Zhang et al 2002) 0.04-1.00 Wood ashes (Erich and Ohno 1992;Saarsalmi et al 2001;Hyt€ onen 2003) 0.90-1.70 Wheat straw ash (Hyt€ onen 2003) 1.30 Rape straw ash (Hyt€ onen 2003) 2.10 Poultry litter ash (Yusiharni 2001;Codling et al 2002) 5.00 Cereal ash (Eichler et al 2008b) 10.4…”
Section: Introductionmentioning
confidence: 99%
“…Concentrations of P in wood ashes are also relatively higher than CFA and range between 0.90 and 1.70% (Demeyer et al, 2001;Saarsalmi et al, 2001;Hyt€ onen, 2003). However, similar to CFA, P in wood ash remains relatively insoluble.…”
Section: Elemental Composition Of Cfamentioning
confidence: 96%